Red-green-bleached redox interfaces in the proximal Permian Cutler red beds: implications for regional fluid alteration - Hullaster, Desiree P.; Soreghan, Gerilyn S.; Kukkadapu, Ravi K.; Dumont, Brock S.; Dee, Kato T.; Elwood Madden, Andrew S. (Frontiers in Earth Science, 2023)
Siliciclastic strata of the Colorado Plateau attract attention for their striking red, green, bleached, and variegated colors that potentially record both early depositional and later diagenetic events. We investigated the proximal-most strata of the Paradox Basin, from their onlap contact with Precambrian basement of the Uncompahgre Plateau to the younger Cutler strata exposed within 10 km of the Uncompahgre Plateau. These strata preserve complex geology associated with buried paleorelief and sediment-related permeability variations. Strata exposed within ~1.5 km of the onlap contact exhibit a pervasive drab color in contrast to the generally red colors that predominate farther from this front. In-between, strata commonly host variegated red/green/bleached intercalations. Mineralogical, geochemical, and textural investigations demonstrate that water-rock interaction charged the rocks with Fe(II) that persists primarily in the phyllosilicate fraction. Color variations reflect grain-size differences that allowed reducing fluids from regional fault and basement/fill contacts to permeate coarser-grained Cutler sediments. Hematite and chlorite occur in both red and green sediments but are absent in the bleached sediments. Pervasive hematite in both red and green layers suggests that sediments were hematite-rich before later alteration. Chlorite and smectite are elevated in green samples and inversely correlated with biotite content. Green coloration is generally associated with (1) coarser grain sizes, (2) spatial association with basement contacts, (3) elevated smectite and/or chlorite, (4) less total Fe but greater Fe(II)/Fe(III) primarily in the phyllosilicate fraction, and (5) uranium enrichment. The bleached coloration is due to removal of pigmentary Fe(III) oxide, while the green coloration is due to the removal of pigmentary hematite and the abundance of Fe(II)-bearing phyllosilicates. Abundant mixed layer and swelling clays such as smectite, illite/smectite, and chlorite/smectite (including tosudite) dominate the mineralogy of the clay fraction. Results are consistent with other studies demonstrating fault-associated fluid alteration in the Paradox Basin region. However, the pervasive greening was not observed in many of these studies and appears to reflect the unique aspects of the paleovalley system and the importance of biotite alteration to Fe(II)-bearing phyllosilicates.